1994
DOI: 10.1021/cr00029a007
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and Dynamics of DNA and Protein-DNA Complexes by 31P NMR

Abstract: Contents 1. Introduction 1315 2. Phosphorus-31 Chemical Shifts 1316 1. Introduction and Basic Principles 1316 2. Theoretical 31P Chemical Shift Calculations 1316 and Empirical Observations 3. Bond Angle Effects 1317 4. Stereoelectronic Effects on 31P Chemical 1318 Shifts 5. Extrinsic and Other Effects on 31P 1318 Chemical Shifts 3. Assignment of 31P Signals of Oligonucleotides 1318 4. 31P Heteronuclear Coupling Constants 1319 5. 31P Melting Curves 1322 6. 31P NMR of Polynucleic Acids 1322 7. 31P NMR of DNA-Dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
232
2

Year Published

1995
1995
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(254 citation statements)
references
References 64 publications
20
232
2
Order By: Relevance
“…Thus, the coupling constants and the 31P chemical shifts both reflects the conformational variations occuring on P4 of (CA) during methylation. This further confirms the suitability of the 31P chemical-shift parameter for the detection of conformational changes in the double-helix backbone (Gorenstein, 1994;El Antri et al, 1993).…”
Section: Noe Analysissupporting
confidence: 69%
“…Thus, the coupling constants and the 31P chemical shifts both reflects the conformational variations occuring on P4 of (CA) during methylation. This further confirms the suitability of the 31P chemical-shift parameter for the detection of conformational changes in the double-helix backbone (Gorenstein, 1994;El Antri et al, 1993).…”
Section: Noe Analysissupporting
confidence: 69%
“…The phosphodiester backbone could be assigned by using 31 (37,38). Although nonstandard phosphodiester conformations could conceptually serve as markers for mismatch recognition, they are unlikely to drive MSH recognition/activation since we observe the B II conformation in both well and poorly recognized sequence contexts (Figs.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, torsion angle restraints for residues at the POU S / Sox2 interface were derived from heteronuclear 3 J couplings (18). The pattern of intramolecular NOEs within the DNA and the distribution of 31 P shifts (44) confirmed that the DNA was predominantly B-form.…”
Section: Methodsmentioning
confidence: 97%